Prediksi Kepuasan Mahasiswa Terhadap Tingkat Pelayanan Menggunakan Algoritma C4.5 (Decision Tree) (Studi Kasus : Fakultas Teknik Universitas Hamzanwadi) - Permana, Baiq Andriska Candra (Infotek : Jurnal Informatika dan Teknologi, 2018)
Universities both state and swaste make various efforts to win the competition in attracting students, among others by providing various facilities and services that can provide satisfaction for students. One of them is the Faculty of Engineering, Hamzanwadi University. This study is aimed at analyzing student satisfaction with the services obtained so far at the Hamzanwadi University Faculty of Engineering using data mining techniques, namely by using C4.5 algorithm or commonly known as the decision tree. Some of the attributes used in this study are to analyze the level of student satisfaction with the services contained in the Faculty of Engineering of the University of Hamzanwadi: costs, facilities, service and loyalty. After the experiments were carried out on datasets obtained from questionnaires for 100 students, the results of accuracy were 81.07%. The classification results using the C4.5 algorithm of 81.07% are considered to be used to measure the level of student satisfaction with services at the Hamzanwadi University Faculty of Engineering.DOI : 10.29408/jit.v1i1.892